2017
DOI: 10.1080/13510002.2017.1343223
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical treatments target kynurenine pathway induced oxidative stress

Abstract: Objective: The objective of this paper was to link the phytochemical and metabolic research treating quinolinic acid induced oxidative stress in neurodegenerative disorders. Methods: Quinolinic acid, a metabolite of the kynurenine pathway of tryptophan catabolism, plays a role in the oxidative stress associated with many neurological disorders and is used to simulate disorders such as Parkinson's disease. Results: In these models, phytochemicals have been shown to reduce striatal lesion size, reduce inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Yet, the role of dietary oxidative stress in the onset, progress, and severity of these diseases is, in most cases, a matter of study. Dietary recommendations for some of these diseases are commonly made, which recognizes the role of food components on the prevention of the disease or alleviation of the symptoms (Arcanjo, Luna, Madruga, & Estevez, ; Parasram, ; Sirota, Gorelik, Harris, Kohen, & Kanner, ; Uttara, Singh, Zamboni, & Mahajan, ). In recent years, sound scientific evidences from studies in experimental animals have contributed to identify the precise pathological mechanisms of dietary protein oxidation products.…”
Section: Pathogenesis Of Dietary Protein Oxidation: Recent Advancesmentioning
confidence: 99%
“…Yet, the role of dietary oxidative stress in the onset, progress, and severity of these diseases is, in most cases, a matter of study. Dietary recommendations for some of these diseases are commonly made, which recognizes the role of food components on the prevention of the disease or alleviation of the symptoms (Arcanjo, Luna, Madruga, & Estevez, ; Parasram, ; Sirota, Gorelik, Harris, Kohen, & Kanner, ; Uttara, Singh, Zamboni, & Mahajan, ). In recent years, sound scientific evidences from studies in experimental animals have contributed to identify the precise pathological mechanisms of dietary protein oxidation products.…”
Section: Pathogenesis Of Dietary Protein Oxidation: Recent Advancesmentioning
confidence: 99%
“…Screening the yeast deletion collection for suppressors of mHTT fragment-induced toxicity revealed that kynurenine 3-monooxygenase (Bna4) deficiency rescues cell viability (Giorgini et al, 2005 ). Metabolites of the kynurenine pathway have been shown to induce oxidative stress and neurological disorders (Pawlak et al, 2009 ; Parasram, 2018 ), which is associated with HD pathophysiology (Stoy et al, 2005 ). Another suppressor screening with gene overexpression, instead of loss-of-function, identified GPxs as potent suppressors of mHTT fragment toxicity (Mason et al, 2013 ).…”
Section: Yeast Models Provide Insights Into Oxidative Stress In Hdmentioning
confidence: 99%
“…As is known to all, inflammation was considered to associate with cancer and oxidative damage ,. In recent years, some antioxidants have been proved to have anti‐inflammatory activities ,,. Antioxidant therapy has become a new anti‐inflammatory therapy .…”
Section: Summery and Outlookmentioning
confidence: 99%
“…Ching 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 3.3 Phenolic Acids and Steroids P. penangianum has few phenolic acids and steroids (Figure 7). Four phenolic acids were purified from the rhizome of P. penangianum, [26] including: (7'Z)-3-O-(3,4-dihydroxy phe-nylethenyl)-caffeic acid (37), protocatechuin acid (38), pmethoxybenzoic acid (39) and p-methoxycinnamaldehyde (40). One phenolic acid, vanillic acid (41) was purified from the aerial parts.…”
Section: Abacopteris Penangiana Chingmentioning
confidence: 99%
See 1 more Smart Citation